2020
DOI: 10.1007/s10620-020-06573-z
|View full text |Cite
|
Sign up to set email alerts
|

Giant Gastric Ulcers: An Unusual Culprit

Abstract: Mycophenolate Mofetil (MMF) is routinely used immunosuppressant in solid organ transplantation is commonly associated with several gastrointestinal (GI) side effects. Here we present a case of giant gastric ulcer of 5 cm from MMF use post cardiac transplant. Case Description A 56-year-old male with history of severe ischemic cardiomyopathy post heart transplant was on immunosuppression with MMF, tacrolimus and prednisone for 5 months. He presented with severe epigastric pain and intermittent episodes of melena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A standard triple therapy, including the proton pump inhibitors (PPIs) and antimicrobial agents, such as amoxicillin, clarithromycin, metronidazole, and levofloxacin, is widely used as the first-line regimen for treatment of Helicobacter pylori infection [1][2][3]. Helicobacter pylori is a microbial carcinogen of gram-negative bacteria, which has been believed to be associated with the development of chronic gastritis, peptic ulcer disease, and gastric cancer (GC), leading dysfunction of inflammation [4][5][6], such as gastric mucosa-associated lymphoid tissue lymphoma (MALT) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A standard triple therapy, including the proton pump inhibitors (PPIs) and antimicrobial agents, such as amoxicillin, clarithromycin, metronidazole, and levofloxacin, is widely used as the first-line regimen for treatment of Helicobacter pylori infection [1][2][3]. Helicobacter pylori is a microbial carcinogen of gram-negative bacteria, which has been believed to be associated with the development of chronic gastritis, peptic ulcer disease, and gastric cancer (GC), leading dysfunction of inflammation [4][5][6], such as gastric mucosa-associated lymphoid tissue lymphoma (MALT) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding (UGIB), a common gastrointestinal disease, usually refers to gastrointestinal bleeding above the Treitz, occurring at the stomach, esophagus, duodenum, and biliary and pancreatic regions (1)(2)(3). Epidemiological studies have found that the mortality rate of this disease is as high as 25-30%, and mainly occurs in adults.…”
Section: Introductionmentioning
confidence: 99%
“… 16 With the development of society and the changes in people’s lifestyles, patients with gastric ulcer bleeding account for the largest proportion of all gastric ulcer complications. 17 Its clinical symptoms include melena, hematemesis, and shock reaction in severe cases 18 , which seriously threatens the life and health of patients. Helicobacter pylori (H. pylori) is present in approximately 50% of the world’s population, with infection levels in developing countries reaching more than 70%.…”
Section: Discussionmentioning
confidence: 99%